Locally confined clonal complexes of mycobacterium ulcerans in two buruli ulcer endemic regions of cameroon - Bolz, Miriam; Vogel, Moritz; Junghanss, Thomas (PLoS neglected tropical diseases, 2015)
Author Summary Buruli ulcer (BU) is a progressively necrotizing disease of the skin, caused by infection with Mycobacterium ulcerans. BU occurs very focally with highest incidence in West Africa. The mode of transmission and the nature and role of potential environmental reservoirs are currently not entirely understood. In this study we sequenced whole genomes of sets of M. ulcerans case isolates from two BU endemic regions in Cameroon. We identified two distinct phylogenetic lineages, which directly correlated with the two endemic regions. Furthermore, we showed that the genetic diversity of M. ulcerans is higher in the older endemic region of Cameroon (Nyong river basin) compared to the more recently emerged infection focus in the same country (Mapé river basin). Together, our results demonstrate that M. ulcerans is developing local clonal complexes by the accumulation of single nucleotide polymorphisms (SNPs) and that these complexes often remain confined to individual endemic foci. The gene encoding for rpoB, which is known to harbour drug resistance mutations against rifampicin in M. tuberculosis, was not affected by SNPs in any of the analysed M. ulcerans strains.
Gesehen am 27.04.2017